Effect of Rapid Thermal Annealing Conditions on the Specific Resistance of the Ohmic Contacts of Ti/Al/Ni/Au Metallization to the GaN/AlGaN Heterostructure - A. D. Yunik; J. A. Solovjov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Effect of rapid thermal annealing conditions on the specific resistance of the ohmic contacts of Ti/Al/Ni/Au metallization with layer thicknesses of 20/120/40/40 nm to the GaN/AlGaN heterostructure with a two-dimensional electron gas on a sapphire substrate has been discovered by transmission line measurement. Rapid thermal annealing of the samples was carried out by the contact heating from the sapphire substrate side in a nitrogen atmosphere at the temperature range from 750 to 1000 °C for 30, 60, and 90 s. It has been discovered that the dependence of the specific contact resistance on the temperature contains two temperature optimums, at which the specific contact resistance of the ohmic contact is less than 1 ⋅  10–4 Ohm⋅ cm2. The appearance of the first temperature optimum is due to the decrease of the distance from the diffusion front of the low-resistance layer of intermetallic compounds formed during the rapid thermal annealing of the Ti/Al/Ni/Au metallization to the region of the two-dimensional electron gas. Outside the first temperature optimum, an increase in the specific contact resistance of up to 9 ⋅  10–3 Ohm⋅ cm2 is observed, due to the absorption of the AlGaN layer by a low-resistance layer of intermetallic compounds, which leads to the degradation of the two-dimensional electron gas under the contacts and deterioration of its conductive properties. The second temperature optimum is due to the passage of the diffusion front of the two-dimensional electron gas region and the establishment of a side contact between the low-resistance intermetallic layer and the two-dimensional electron gas, which leads to the decrease in the specific contact resistance. With an increase in the fast thermal annealing time from 30 to 90 s the shift of the interval of the first temperature optimum from 800 to 775 °C for the lower boundary and from 825 to 800 °C for the upper boundary, and for the second temperature optimum from 875 to 850 °C for the lower boundary, and from 950 to 875 °C for the upper boundary is observed, which is due to an equivalent increase in the diffusion depth of the Ti/Al/Ni/Au metallization components. The results obtained can be used in the technology for creating GaN-based products with a two-dimensional electron gas.